Immigrant Child Legal Identity Registration as A Tool to Promote Sustainable Development Goals 16.9 - Mouva Putri Ramadhita; Rianda Dirkareshza (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
Immigrant child in Indonesia and other nation surely has to reach their rights, including in the provision of legal identity, and this matter is stated in as the 16.9th goal of the SDGs. Child registration is an important document that every single child should acknowledge and own as well as identical form and an integral part of citizens’ civil and political rights. However, Indonesia only focuses on immigrant mandatories and has not discussed the fate of child immigrants in terms of identity on granting their rights. This paper intends to find the urgencies on immigrant child legal identity registration in Indonesia and provide a law comparison to maximize the legal identity regulation for immigrants as their basic rights. This paper uses a normative juridical and comparative approach that scopes the immigrant child’s legal identity registration in order to reach the 16.9th SDGs and fulfill the basic rights of the immigrant child that should be reached by them as human beings. The findings of the research show that some immigrant child still not able to reach the 16.9th SDGs goal. Some regulations in Indonesia are not able to scope the loopholes in the societies., Moreover, sustainable development is an important goal for societies that surely fulfill basic rights, and Indonesia, compared with the United States of America and China, has no scope for basic regulation for the immigrant child, regarding legal identity registration.